An authoritarian parenting: main predictor in temper tantrum of pre-school children - Rusana; Ida Ariani; Erna Sari (UM Purwokerto Press, 2020)
Temper tantrum is an emotional condition related to the behavior of preschool children. Tantrums will be problematic if it’s excessive and even injurious behavior. Several factors caused tantrums such as physiological, psychological, parental and environmental factors.The aim of this study was to analyze the dominant factors between parental factors (parenting, communication, occupation and gender), child factors (gender, education level) and family environmental factors (number of children under five, families living at home) with temper tantrums for pre-school children. . Analytical survey research and cross sectional design. The sample size was 120 parents and pre-school children using cluster random sampling technique. Bivariate analysis used the chi square test, while multivariate analysis used multiple logistic regression. The results showed that the parenting style was the main predictor related to the temper tantrums of preschool children (pv = 0,001) with an OR= 14.879 controlled by variables of occupation and families live at home.In conclusion authoritarian parenting style causes temper tantrums 14.8 times higher than democratic parenting in pre-school children.